Patterns of Sexual Size Dimorphism in Chelonia : Revisiting Kinosternidae (2014)
ABSTRACT: Rensch’s rule, a macroevolutionary pattern in which sexual size dimorphism (SSD) increases with body size in male-biased SSD species, or decreases with female-biased SSD species, has been investigated in many vertebrates because it indicates whether SSD is being driven by sexual selection or a different force (i.e. fecundity or natural selection). Evidence in turtles has shown some conflicting results, which may be explained by the different phylogenies used in the analyses. Because the newly available well-resolved phylogeny of family Kinosternidae provides evidence for the ancient monophyly of Staurotypidae and Kinosternidae and their recognition as separate families (previously Staurotypidae was considered as a subfamily within Kinosternidae) and introduced the genus Cryptochelys for the monophyletic leucostomum clade, we revisit the pattern of SSD and body size in Kinosternidae. By contrast to what had been proposed, we found that the Kinosternidae as formerly recognized (i.e. including Staurotypus and Claudius) and the restricted Kinosternidae both follow a pattern consistent with Rensch’s rule. Our analysis with published body size data did not change our results, confirming the importance of the phylogeny used in macroevolutionary studies.